1988
DOI: 10.1537/ase1911.96.319
|View full text |Cite
|
Sign up to set email alerts
|

Incidences of cranial nonmetric characters in five jomon populations from west Japan.

Abstract: Incidence data of thirty cranial nonmetric characters were presented for five Jomon population samples of West Japan as well as for protohistoric Kofun sample of west Japan and modern Kinki, Hokuriku, Okinawa-Amami, Sakhalin Ainu, and Korea-China samples, and data of 19 characters for Sakishima samples.COCHRAN'S tests show significant sex differences for 14 or at least 10 of 30 characters.Interpopulation comparisons were performed by applying metric multidimensional scaling analysis (MMDSA) to mean character d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0
1

Year Published

1991
1991
2007
2007

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 17 publications
2
27
0
1
Order By: Relevance
“…The consensus of physical anthropologists is that a certain morphological difference exists between the Sakhalin Ainu and the Hokkaido Ainu (HIRAI, 1927;KODAMA, 1940KODAMA, , 1970 KIYONO, 1949;YAMAGUCHI, 1973;MOURI, 1988). HIRAI (1927) and KIYONO (1949) claimed that the Sakhalin Ainu were a genuine population and had not intermarried to any great degree with other tribes, because their craniometric studies showed that the Sakhalin Ainu were not very close to the Neolithic Jomon, Hokkaido Ainu nor modern Japanese and the variances of their metric traits were fairly small.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The consensus of physical anthropologists is that a certain morphological difference exists between the Sakhalin Ainu and the Hokkaido Ainu (HIRAI, 1927;KODAMA, 1940KODAMA, , 1970 KIYONO, 1949;YAMAGUCHI, 1973;MOURI, 1988). HIRAI (1927) and KIYONO (1949) claimed that the Sakhalin Ainu were a genuine population and had not intermarried to any great degree with other tribes, because their craniometric studies showed that the Sakhalin Ainu were not very close to the Neolithic Jomon, Hokkaido Ainu nor modern Japanese and the variances of their metric traits were fairly small.…”
Section: Discussionmentioning
confidence: 99%
“…However, KODAMA (1940KODAMA ( , 1970, gathering a large skeletal collection of the Ainu, stated that the characteristics of the Sakhalin Ainu, consisting of large facial height, low cranial height, flat nasal bone and a high incidence of supraorbital foramen, must have been caused by frequent intermixture with the Oroch and Gilyak in former times. KODAMA's position now gets support from anthropologists who have recently reexamined the Sakhalin Ainu in terms of craniometry, face-flatness, osteometry and nonmetric traits (YAMAGUCHI, 1973;MIZOGUCHI, 1986;MOURI, 1986MOURI, , 1988DODO, 1987;TAGAYA, 1987).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is generally agreed, based on cranial and dental morphology, that Jomon period populations are direct ancestors of the Hokkaido Ainu (e.g. Howells, 1966;Turner, 1976;Brace and Nagai, 1982;Yamaguchi, 1982;Hanihara, 1985Hanihara, , 1991Dodo, 1986;Mouri, 1986;Matsumura, 1989Matsumura, , 1994Matsumura, , 1995aDodo and Ishida, 1990;Pietrusewsky, 1994Pietrusewsky, , 2004Ossenberg et al, 2006). Geographical variation in Jomon period material has been investigated by several researchers and only minor differences have been found in the cranial morphology of samples dating from the middle to final Jomon periods (ca.…”
Section: Introductionmentioning
confidence: 99%
“…The classification of the Cercopithecidae by Strasser and Delson (1987) is used at and above the (sub-) generic level and with a few minor modifications. Table 1 shows the data for the skeletal composition of the lacrimal fossa of the Old World monkeys observed in this study as well as the data from Benefit and McCrossin (1993), which are entered separately in the table because of the different sampling procedures (Green et al, 1980;Korey, 1980;Mouri, 1988). Benefit and McCrossin (1993) sort the lacrimal fossae into three patterns, that is, the maxillalacrimal (M-L), the intermediate (Int), and the exclusively lacrimal (Lac).…”
Section: Allmentioning
confidence: 99%